Service learning as a method of university impact on public knowledge. Case study of University students' contributions to Wikipedia - Pečarić, Đilda (2012)
Modern universities have four basic tasks that have to offer to students: studying, training, research and active citizenship. Since it is already known that Service Learning (SL) method fulfills two tasks - training and active citizenship, the goal of this paper is to discuss if SL method fulfills other two tasks of modern universities studying and research? In order to obtain the answer to this question we surveyed the students who were given the assignment to write and put an article on Wikipedia. Students’ answers indicate that SL method fulfills all four tasks of modern universities: studying, training, research and active citizenship. At the same time, the choice of the project, more precisely the writing of an article for Wikipedia, realizes the impact of service learning method on public knowledge.
Projekt MZOS
ENG